Effect of N-Methyl-D-Aspartate Receptor Blockade on Anxiety-Like Behavior Induced in Rats by Postnatal Chronic Exposure to the Endocrine Disruptor Di-2 (Ethyl-Hexyl Phthalate) in Elevated plus Maze Test - Carbone, Silvia Elena (2019)
Di-2-Ethylhexyl Phthalate (DEHP) is the widely used to convey flexibility and transparency to plastic products made of polyvinyl chloride and also in the manufacture of medical devices. DEHP disrupts reproductive tract development in an antiandrogenic manner and also may induce neurobehavioral changes. In previous works, we demonstrated that chronic postnatal exposure to DEHP alters the neuroendocrine regulation of the testicular axis, modifying the hypothalamic concentration of excitatory neurotransmitters and therefore induces an anxiogenic effect. In the Elevated Plus Maze (EPM) test, dizocilpine (MK-801) induces a decrease in anxiety-related behaviors throughout NMDA receptor blockade. The objective of this work was to investigate whether the blockade of NMDA receptors of glutamate by the non-competitive antagonist MK-801 could modify the anxiety-like behavior induced by chronic postnatal exposure to DEHP (30 mg/kg body weight/day, orally from birth) in young adult male rats in the EPM test. The results show that NMDA receptor blockade by MK-801 (0.1 mg/kg body weight, i.p.) in DEHP exposed animals is able to produce a significant decrease in time spent in closed arms (TSC) and in Freezing Time (FT) as well as an increase in time spent in open arms (TSO) in the EPM test, indicating an anxiolytic effect. In conclusion, our results suggest: 1) NMDA receptor blockade by MK-801 can reverse anxiety-like behavior induced by exposure to DEHP during the early period of life. 2) The glutamatergic system is involved in the anxiogenic effect of phthalate, which is probably triggered by its known antiandrogenic action.